Altered Tissue Distribution and Elimination of Amikacin Encapsulated in Unilamellar, Low-Clearance Liposomes (MiKasome®) - Fielding, Robert M.; Lewis, Ramilla O.; Moon-McDermott, Lotus (Pharmaceutical research, 1998)
Amikacin in small unilamellar liposomes (MiKasome) has prolonged plasma residence (half-life > 24hr) and sustained efficacy in Gram-negative infection models. Since low-clearance liposomes may be subject to a lower rate of phagocytic uptake, we hypothesized this formulation may enhance amikacin distribution to tissues outside the mononuclear phagocyte system. Rats received one intravenous dose (50 mg/kg) of conventional or liposomal amikacin. Amikacin was measured for ten days in plasma, twelve tissues, urine and bile. Liposomal amikacin increased and prolonged drug exposure in all tissues. Tissue half-lives (63-465 hr) exceeded the plasma half-life (24.5 hr). Peak levels occurred within 4 hours in some tissues, but were delayed 1-3 days in spleen, liver, lungs and duodenum, demonstrating the importance of characterizing the entire tissue concentration vs. time profile for liposomal drugs. Predicted steady-state tissue concentrations for twice weekly dosing were >100 microg/g. Less than half the liposomal amikacin was recovered in tissues and excreta, suggesting metabolism occurred. Amikacin was not detected in plasma ultrafiltrates. Tissue-plasma partition coefficients (0.2-0.8 in most tissues) estimated from tissue-plasma ratios at Tmax were similar to those estimated from tissue AUCs. Low-clearance liposomal amikacin increased and prolonged drug residence in all tissues compared to conventional amikacin. The long tissue half-lives suggest liposomal amikacin is sequestered within tissues, and that an extended dosing interval is appropriate for chronic or prophylactic therapy with this formulation.